PENGARUH PROMOSI, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SONY (STUDI KASUS PADA PENGGUNA SMARTPHONE SONY DI UNIVERSITAS DIPONEGORO SEMARANG) - Fernando Ginting; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
The needs of contemporary society about communication has become a basic requirement. Connectivity is unavoidable in this modern era. Mobile phone or smartphone has taken a prominent position for everyone throughout the world, smartphone not only use for communication but also become the media to get information, make a creativity until make a transaction. Sony is one of the most trusted brand of smartphones in the world, but in it is development, another brand product providers smartphone is getting more from year to year, which makes the sales of Sony smartphone decreased, especially in Semarang city. The purpose of this research is to know the influence of promotion, brand image, and the quality of products towards purchasing decisions smartphone Sony at Diponegoro University. The type of this research is explanatory research. The population in this research is the students that still active in Diponegoro University with the number of samples is 100 respondents. Sampling using a purposive sampling. The measurement scale using the Likert scale. Methods of analysis that used is cross tabulations, correlation, determination, simple linear regression, multiple liniear regression, t-test, and F-test using SPSS program version 20. Based on the results of the research known that promotion, brand image, and quality of the product have a positive effect and make a significant effect on purchasing decisions, either partially or simultaneously. Free variables that have the most influence on purchasing decision is the variabel quality of the product. And the advice that can be given is make a sustained promotional products of Sony smartphone by giving direct discounts and giving additional completeness of smartphones, doing promotions with special price for consumers who be the first purchases at the Sony official store or for consumers that booking earlier through official website of Sony, product of smartphone Sony retains it’s product price but improve the quality of the product and the benefits that provided so the consumers that using smartphone Sony have their own pride, Sony may update or complete the features that became a mainstay of smartphone Sony that not often in an error, add a service center in each city and giving a special training to employees.